The lived experience of female genital cutting (FGC) in Somali-Canadian women's daily lives. - Danielle Jacobson; Emily Glazer; Robin Mason; Deanna Duplessis; Kimberly Blom; Janice Du Mont; Navmeet Jassal; Gillian Einstein (PLoS ONE, 2018)
Many of the Somali women who have immigrated to other countries, including Canada, have experienced Female Genital Circumcision/ Mutilation/ Cutting (FGC). While there is literature on the medical aspects of FGC, we were interested in understanding the daily life experiences and bodily sensations of Somali-Canadian women in the context of FGC. Fourteen women living in the Greater Toronto Area were interviewed. Interview data were analyzed using a phenomenological approach. We found that the memory of the ceremonial cutting was vivid but was frequently described with acceptance and resignation-as something that just is; that was normal given the particular context, familial and cultural, and their young age. Most of the women recounted experiencing pain and discomfort throughout their adult lives but were intent on not noticing or giving the pain any power; they considered themselves healthy. The following themes emerged from our interviews: Every Body Had It: Discussing FGC, I'm Normal Aren't I?, and Feeling in My Body-all themes that work at normalizing their bodies in a society that they know views them as different. They dealt with both pain and pleasure in the context of their busy lives suggesting resilience in spite of the day-to-day difficulties of daily life.